Panda Tourism: The role of destination image on the relationship between tourists’ consumption values and behavioural intention / Norsuhana Mazaruddin and Faiz Izwan Anuar - Mazaruddin, Norsuhana; Anuar, Faiz Izwan (Universiti Teknologi MARA, Negeri Sembilan, 2019)
The Malaysian government received two endangered pandas as a diplomatic gift from the government of China to mark 40 years of strong diplomatic ties between the two countries. The Giant Panda Conservation Centre (GPCC) in Zoo Negara was established to show Malaysia’s commitment towards China’s governmental efforts in increasing the number of the endangered giant panda worldwide and establishing a distinctly new niche tourism attraction called Panda Tourism (PT).The attraction has pulled many local and international visitorsfromdifferent countries across Asia, Europe, North America, and Australia. However, research on the rationale, benefits, issues, and future ofPT initiative remains under-explored. The present study attempts to understand the PT conceptby measuring the consumption value dimensions of PT, namely; functional, social, emotional, epistemic and conditional and how these dimensions affect tourists behavioural intention to visit other PTsthroughout the world. In addition, the study measured the mediation effect of destination image toward the relationship of consumption values and tourists behavioural intention. The findings of this study are among the early attempts to better understand the rationales, benefits, and potentials of PTas a niche tourism concept in Malaysia.The study employed the survey questionnaire to gather quantitative data. Data were analyzed using the SmartPLS 3.0 software. The results of the analysis identified conditional, functional, and social as the significant determinants of Consumption Value towards tourists’ behavioural intention to visit PT.Furthermore, functional value proved to have significant direct as well as indirect influence on the tourists’ behavioural intention.